Analysis of RADEC Learning Model in Improving Students Learning Outcomes at SD Negeri Karangjengkol 01, Kesugihan, Cilacap - Puput Lestari; Kuntoro Kuntoro (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to analyze the application of the RADEC (Reading, Answering, Discussing, and Explaining) learning model in improving student learning outcomes at SD Negeri Karangjengkol 01, Kesugihan, Cilacap. The approach used in this study is descriptive qualitative research, which focuses on understanding the learning process and its impact on student learning outcomes. Data were collected through interviews with teachers, direct observation of learning activities, and document analysis in the form of student learning outcomes. The results of the study indicate that the application of the RADEC model can improve student learning outcomes, especially in terms of understanding subject matter and communication skills. Through reading, answering, discussing, and explaining activities, students more active and involved in the learning process, which leads to improved learning outcomes. In addition, the application of this model can also increase students learning motivation, making them more interested and enthusiastic in participating in learning. Based on these findings, it is suggested that the RADEC learning model can be applied more widely in elementary schools to improve the effectiveness and quality of learning.